Golden score period in high-level judo competitions: the effect of the scores and penalties at the real contest time - Ceylan, B.; Öztürk, F.; Taskin, H. B.; Balci, S. S. (International Journal of Performance Analysis in Sport, 2025)
This study investigated the effect of scores and penalties in real contest time on the contest results in the golden score period. Of 6872 official contests at 10 different high-level competitions, 1414 contests with a golden score (21%) were included. Analyses for sex, weight category and rounds were performed with total match duration. Scores and penalties were recorded separately for real contest time and golden score period. Mutual waza-ari at real time (first 4 min) caused the high rate of matches ending with a score (p < 0.05). The rate of receiving a shido was higher among defeated athletes during the real contest time (p < 0.05). The rate of winning a contest with score during the golden score period was lower than winning a contest with hansoku-make in heavyweight categories. The contests more likely ended with scores and less likely ended with hansoku-make for men than women (p < 0.05). The results showed that the way the contest ended was different between sexes and among weight categories during the golden score period. Receiving a shido during the real contest time can lead to defeat in the golden score, thus athletes should be careful of presenting active judo and refraining from any action leading to penalties.